Inkjet printed uniform quantum dots as color conversion layers for full-color OLED displays - Hu, Zhiping; Yin, Yongming; Ali, Muhammad Umair; Peng, Wenxiang; Zhang, Shijie; Li, Dongze; Zou, Taoyu; Li, Yuanyuan; Jiao, Shibo; Chen, Shu-Jhih; Lee, Chia-Yu; Meng, Hong; et al. (Nanoscale, 2020)
Quantum dots (QDs) have shown great potential for next generation displays owing to their fascinating optoelectronic characteristics. In this work, we present a novel full-color display based on blue organic light emitting diodes (BOLEDs) and patterned red and green QD color conversion layers (CCLs). To enable efficient blue-to-green or blue-to-red photoconversion, micrometer-thick QD films with a uniform surface morphology are obtained by utilizing UV-induced polymerization. The uniform QD layers are directly inkjet printed on red and green color filters to further eliminate the residual blue emissions. Based on this QD-BOLED architecture, a 6.6-inch full-color display with 95% Broadcasting Service Television 2020 (BT.2020) color gamut and wide viewing-angles is successfully demonstrated. The inkjet printing method introduced in this work provides a cost-effective way to extend the applications of QDs for full-color displays.